A Proposed Framework for Hypertension in Mauritius - Sooklall, Raginee; Tengnah, Muhammad Ali Javed; Nagowah, Soulakshmee Devi (Journal of Health Informatics in Africa, 2018)
Non communicable diseases like Hypertension, also known as high blood pressure, is considered to be one of the biggest contributors to the global death rate. According to the latest data published in May 2014 by the World Health Organisation (WHO), death rate by hypertension has reached up to 6.39%, whereby age adjusted death rate is 38.18% per 100,000 of population, ranking Mauritius twelfth in the world among the countries having a high percentage of cause of death by hypertension. This paper analyses existing mobile applications and frameworks used for managing hypertension and proposes a new framework for Mauritius. According to the European Society of Hypertension (ESH), the use of electronic blood devices for blood pressure measurement such as ambulatory blood pressure monitors and smartphone applications have reinforced blood pressure monitoring and diagnosis. The framework therefore comprises of a smart mobile application which takes readings of systolic and diastolic blood pressures on a daily basis and makes use of intelligent techniques to conclude whether the patient is hypertensive or not. Components such as Stress Management and Dash Diet Recommender are integrated in the framework.